2013
DOI: 10.1021/jm400072p
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase Inhibitor Design by Targeting the Asp-Phe-Gly (DFG) Motif: The Role of the DFG Motif in the Design of Epidermal Growth Factor Receptor Inhibitors

Abstract: The Asp-Phe-Gly (DFG) motif plays an important role in the regulation of kinase activity. Structure-based drug design was performed to design compounds able to interact with the DFG motif; epidermal growth factor receptor (EGFR) was selected as an example. Structural insights obtained from the EGFR/2a complex suggested that an extension from the meta-position on the phenyl group (ring-5) would improve interactions with the DFG motif. Indeed, introduction of an N,N-dimethylamino tail resulted in 4b, which showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(68 citation statements)
references
References 69 publications
5
63
0
Order By: Relevance
“…In addition to its presumed interaction with the MET769 residue, BDMC-A was found to be able to undergo an additional H-bond interaction with the DFG loop of the ASP831 residue. Recently, furano-pyrimidine EGFR kinase inhibitors were shown to specifically interact with this DFG loop and to modify the kinase activity [54,55]. Additionally, we found that BDMC-A exhibits higher docking and free binding energy scores compared to curcumin.…”
Section: Discussionmentioning
confidence: 64%
“…In addition to its presumed interaction with the MET769 residue, BDMC-A was found to be able to undergo an additional H-bond interaction with the DFG loop of the ASP831 residue. Recently, furano-pyrimidine EGFR kinase inhibitors were shown to specifically interact with this DFG loop and to modify the kinase activity [54,55]. Additionally, we found that BDMC-A exhibits higher docking and free binding energy scores compared to curcumin.…”
Section: Discussionmentioning
confidence: 64%
“…This is similar to the vertical and horizontal bound conformations observed for other furo[2,3- d ]pyrimidines in crystal structures with RTKs. 50 The energy difference between the best docked horizontal pose of 11 was within 2 kcal/mol of the lowest energy vertical docked pose in both VEGFR-2 crystal structure and the PDGFR-β homology model. The horizontal pose conformationally orients the phenyl ring of the aniline group towards the 5-position of the furo[2,3- d ]pyrimidine as demonstrated by a 1 H NMR study (see below).…”
Section: Molecular Modeling and Computational Studiesmentioning
confidence: 86%
“…The choice of any one should be fine, though the selection of chain A was a little arbitrary. At the time of analysis 49 EGFR structures of kinase domain were obtained: 1M14, 1M17,[17] 1XKK,[18] 2EB2, 2EB3, 3UG1, 3UG2, 3VJN, 3VJO,[19] 2GS2, 2GS7,[20] 2ITN, 2ITO, 2ITP, 2ITQ, 2ITT, 2ITU, 2ITV, 2ITW, 2ITX, 2ITY, 2ITZ, 2J6M,[21] 2JIT, 2JIU,[9] 2RF9, 2RFD, 2RFE,[22] 2RGP,[23] 3BEL,[24] 3GT8,[25] 3LZB,[26] 3POZ,[27] 3W2O, 3W2R, 3W2S,[28] 3W32, 3W33,[29] 4HJO,[7] 4I1Z, 4I20, 4I21, 4I22, 4I23,[8] 4JQ7, 4JQ8, 4JR3, 4JRV,[30] 4LI5. [31]…”
Section: Methodsmentioning
confidence: 99%